The efficacy of microendoscopic discectomy in reducing iatrogenic muscle injury - Shin, Dong Ah; Kim, Keung Nyun; Shin, Hyun Cheol; Yoon, Do Heum (Journal of neurosurgery. Spine, 2008)
The objective of this study was to evaluate the invasiveness of microendoscopic discectomy (MED) in comparison with microscopic discectomy (MD) by measuring serum levels of creatine phosphokinase (CPK)-MM and lactate dehydrogenase (LDH)-5, and by comparing visual analog scale (VAS) scores of postoperative pain. This study included a group of 15 patients who underwent surgery using MED and 15 patients who underwent surgery using MD, both for single-level unilateral herniated nucleus pulposus. The CPK-MM and LDH-5 levels were measured at admission and after 1, 3, and 5 days postoperatively. Pain assessment was recorded using scores raging from 0 to 10 on a subjective VAS at admission and at 1, 3, and 5 days postoperatively. The mean CPK-MM levels were lower for the MED group than for the MD group at both 3 (576.1 +/- 286.3 IU/L compared with 968.1 +/- 377.8 IU/L) and 5 days (348.1 +/- 231.0 IU/L compared with 721.7 +/- 463.2) postoperatively (p < 0.05). The mean VAS scores for postoperative back pain were lower in the MED group than in the MD group, both at 1 (3.3 +/- 2.3 compared with 5.8 +/- 1.5) and 5 days (1.9 +/- 1.1 compared with 3.6 +/- 1.1) postoperatively (p < 0.01). The MED procedure is less invasive than MD, and causes less muscle damage and less back pain.